Clinical and microbiological response of mice to intranasal inoculation with Lactococcus lactis expressing Group A Streptococcus antigens, to be used as an anti‐streptococcal vaccine. (21st November 2018) - García, Patricia C.; Paillavil, Braulio A.; Scioscia, Natalia; Dale, James B.; Legarraga, Paulette; Salazar‐Echegarai, Francisco J.; Bueno, Susan M.; Kalergis, Alexis M.; Wozniak, Aniela
ABSTRACT: Protein subunit vaccines are often preferred because of their protective efficacy and safety. Lactic acid bacteria expressing heterologous antigens constitute a promising approach to vaccine development. However, their safety in terms of toxicity and bacterial clearance must be evaluated. Anti‐ Streptococcus pyogenes ( S. pyogenes ) vaccines face additional safety concerns because they may elicit autoimmune responses. The assessment of toxicity, clearance and autoimmunity of an anti‐streptococcal vaccine based on Lactococcus lactis ( L. lactis ) expressing 10 different M protein fragments from S. pyogenes (L. lactis‐ Mx10) is here reported. Clearance of L. lactis from the oropharynges of immunocompetent mice and mice devoid of T/B lymphocytes mice was achieved without using antibiotics. The absence of autoimmune responses against human tissues was demonstrated with human brain, heart and kidney. Assessment of toxicity showed that leucocyte counts and selected serum biochemical factors were not affected in L. lactis ‐Mx10‐immunized mice. In contrast, mice immunized with L. lactis wild type vector ( L. lactis ‐WT) showed increased neutrophil and monocyte counts and altered histopathology of lymph nodes, lungs and nasal epithelium. Two days after immunization, L. lactis‐ Mx10‐immunized and L. lactis‐ WT‐immunized mice weighed significantly less than unimmunized mice. However, both groups of immunized mice recovered their body weights by Day 6. Our results demonstrate that L. lactis ‐WT, but not the vaccine L. lactis ‐Mx10, induces alterations in certain hematologic and histopathological variables. We consider these data a major contribution to data on L. lactis as a bacterial vector for vaccine delivery.